Empowering Excellence: The Impact of Transformational Leadership and Knowledge Transfer on Teacher Performance - Qristin Violinda; Ahmad Alfiyan Abdul Majid; Ira Setiawati (Green Economics Review, 2024)
The objective of this research is to analyze the impact of transformational leadership, knowledge transfer, and work motivation on the performance of high school teachers. Utilizing a sample of 108 respondents selected through a Non-Probability Sampling technique, the study employed Multiple Linear Regression Analysis for data evaluation. The results indicate that Transformational Leadership (X1) has a positive and significant effect on teacher performance (Y), with a significance value of 0.028 (p < 0.05) and a t-value of 2.226, exceeding the critical t-value of 1.983. Similarly, Knowledge Transfer (X2) positively influences teacher performance (Y) with a significance value of 0.000 (p < 0.05) and a t-value of 6.602, which is greater than the critical t-value. In contrast, Work Motivation (X3) does not have a significant effect on teacher performance (Y), as indicated by a significance value of 0.062 (p > 0.05) and a t-value of 1.886, which is less than the critical t-value. In conclusion, the findings demonstrate that Transformational Leadership and Knowledge Transfer positively and significantly influence teacher performance, while Work Motivation does not significantly affect it.